Study on interfacial debonding expansion in buoyancy material integrated structure of underwater vehicle based on cohesive zone model - Wenhua HUANG; Piao LI; Xu LI; Dong HUANG (Zhongguo Jianchuan Yanjiu)
ObjectiveIn order to effectively evaluate the safety and integrity of buoyancy material integrated structures in underwater vehicle under service conditions in deep water, the generation and propagation of debonding at the interface between steel and buoyancy materials were studied using experimental and simulation methods. Methods First, the mechanical parameters of the material interface are measured through standard tests and numerical calibration, and a cohesive zone model for stimulating interface failure is constructed. Then, based on finite element simulation, regions of high stress gradients and locations prone to damage are estimated through global stress/deformation analysis, and the expansion path and mode of debonding are determined through submodel simulation. Results Interface debonding tends to occur at the top of the circumferential partition frame within the integrated structure, mainly in I-type, extending along the circumferential direction and towards the outer surface. Conclusions Simulation analysis reveals the interface failure position and evolution, providing a basis for simulating interface failure under complex working conditions and optimizing interface performance in the future.